Analisis Pengaruh Penambahan Aerasi dan Variasi Waktu Fitoremediasi Menggunakan Tumbuhan Myriophyllum aquaticum pada Effluent IPAL Komunal Desa Sungai Langka - Ruben Thomson Napitupulu; Irhamni; Suci Wulandari (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Sungai Langka Village has a communal Wastewater Treatment Plant (WWTP) building, but the treated effluent still does not accordance the quality standards set by the Regulation of the Minister of Environment and Forestry Number 68 of 2016 concerning Domestic Wastewater Quality Standards. Phytoremediation was chosen as an environmentally friendly and easily applicable method. The selection of Myriophyllum aquaticum was due to its phytodegradation ability in breaking down organic and inorganic substances, as well as its abundance of bacteria that can absorb nutrients in the wastewater. This study used four reactors: Reactor A1 (control), Reactor A2 (phytoremediation), Reactor A3 (aeration), and Reactor A4 (phytoremediation and aeration). The results of this study showed that over time, the efficiency in reducing the ammonia parameter increased, with the following efficiencies recorded on day 15: Reactor A1 at 98.95%, Reactor A2 at 98.59%, Reactor A3 at 98.90%, and Reactor A4 at 98.15%. The results of statistical testing using multiple linear regression showed that the efficiency of ammonia parameter reduction was significantly affected by time variation, whereas the addition of aeration did not have a significant effect.